2016
DOI: 10.1057/s41268-016-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

Boundary organizations in regime complexes: a social network profile of IPBES

Abstract: Regime complexes are arrays of institutions with partially overlapping mandates and memberships. As tensions frequently arise among these institutions, there is a growing interest geared to finding strategies to reduce them. Insights from regime theory, science and technology studies, and social network analysis support the claim that "boundary organizations"—a type of organization until now overlooked in International Relations—can reduce tensions within regime complexes by generating credible, legitimate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 88 publications
(87 reference statements)
0
28
0
Order By: Relevance
“…traditional and local knowledge.' However, as previous studies have shown, this directive on knowledge diversity has hitherto had little impact, there being instead a great bias in favor of not only scientific expertise but also expertise based in the natural sciences (Heubach and Lambini 2017;Montana 2017;Montana and Borie 2016;Morin et al 2017;Stenseke 2016;Timpte et al 2017). The definition of who is able to become an IPBES expert, and what kind of expertise is expected of such an actor, are thus regulated in the organizational structure (UNEP 2012) and rules of procedure (IPBES 2013c).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…traditional and local knowledge.' However, as previous studies have shown, this directive on knowledge diversity has hitherto had little impact, there being instead a great bias in favor of not only scientific expertise but also expertise based in the natural sciences (Heubach and Lambini 2017;Montana 2017;Montana and Borie 2016;Morin et al 2017;Stenseke 2016;Timpte et al 2017). The definition of who is able to become an IPBES expert, and what kind of expertise is expected of such an actor, are thus regulated in the organizational structure (UNEP 2012) and rules of procedure (IPBES 2013c).…”
Section: Discussionmentioning
confidence: 99%
“…Not only social science, but also indigenous and local knowledge should be part of the assessment work; IPBES aims to 'bring different knowledge systems, including indigenous systems, into the sciencepolicy interface ' (UNEP 2012, 13). This ambitious goal, however, has been easier to declare than to achieve; IPBES experts are still disproportionally dominated by natural scientists (Heubach and Lambini 2017;Montana 2017;Montana and Borie 2016;Morin et al 2017;Timpte et al 2017). It is important to note that the first cohort of IPBES fellows reflects a somewhat broader range of expertise; even if its composition is far from balanced, it nevertheless includes more social scientists, more women, and better regional spread than are found among the IPBES experts.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of this new knowledge needs involvement and collaboration between IPBES's participants, including stakeholders. Although Morin et al (2016) studied interdependencies between experts of the multidisciplinary expert panel (MEP) and bureau members of IPBES, we suggest focusing on IPBES's stakeholders. The inclusiveness of IPBES can thus be analyzed by studying the exchange of knowledge and expertise through advice-seeking and advice-giving.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus not possible to generalize our results to the whole institution. Further research may deal with other segments of IPBES such as MEP and bureau members (Morin et al 2016), task forces, or country delegations. We show that the leadership http://www.ecologyandsociety.org/vol22/iss1/art11/ dynamics managed by the IPBES secretariat convey a precise participation model, which tends either to enrol the stakeholders involved or leads them to self-exclude themselves from the group.…”
Section: Introductionmentioning
confidence: 99%